Legal Considerations About Social Property In Peru - Bustamante, Luis (1973)
The purpose of this work is concrete: starting from an outline of the traditional property system of our country, it looks for its sediment in the legal institution of property to contrast it with the official references to the new economic sector formed by enterprises of social property which will be established soon. This with the aim of finding the notes that is possible to attribute it and those that must be discarded.